Zakat institutions’ Mustahiq transformation in developing countries: Comparison study - Muhammad Nafik Hadi Ryandono, Ida Wijayanti, (Opción, 2020)
The zakat institution is one of the institutions to improve the economy of the people in developing countries with the Muslim population majority. The transformation process of Mustahiq is one indicator of the success of the zakat institution in realizing equity and the distribution of income, the creation of justice and the nation’s social welfare. The purpose of this study was to determine the ratio of mustahiq transformation that occurred to zakat institutions in Indonesia and Brunei Darussalam. Results showed that the Mustahiq transformation rate increased in different portions for each zakat institution in Indonesia and Brunei Darussalam